A New Cyphocharax from the Lower Rio Tapajos, Amazon Basin, Brazil (Characiformes: Curimatidae) - Bortolo, Gustavo C.; Lima, Flavio C. T.; Melo, Bruno F. [UNESP] (Amer Soc Ichthyologists & Herpetologists, 2018)
A new species of Cyphocharax (Characiformes: Curimatidae) is described from the lower Rio Tapajos basin, including its tributary, the Rio Arapiuns, Para, Brazil. The new species is diagnosed from congeners by a combination of characters that includes overall body light-colored, with a silvery hue, lacking any pattern of stripes or blotches, a distinctly straight body profile, and some meristic and morphometric features. Comparisons with similar congeners as Cyphocharax festivus, Cyphocharax leucostictus, Cyphocharax nigripinnis, and Cyphocharax plumbeus, some of which occur sympatrically with the new species, are presented.